Trenbolone residue in tissues and urine of Onggole male calves treated with acetate trenbolone implant - R Widiastuti; R Firmansyah; Indraningsih . (Jurnal Ilmu Ternak dan Veteriner, 2007)
Trenbolone acetate (TBA) is a hormone being permitted to be used as growth promoters for livestocks in several meat-exporting countries. The presence of trenbolone residu in animal products might affect human health. The purpose of this study was to determine the distribution of trenbolone residue (TBA dan 17 ß-trenbolone) in tissues and urine of Onggole male calves. The implantation of 200 mg TBA as Finaplix-H® was done subcutaneously on the back side of the medial part of ear. Urine were collected periodically until 21 days post implantation. The animals were terminated on the day 21st post implantation. Urine, meat and organs were analysed for trenbolone residues. The results showed that TBA residues were detected in tissues of inner and surrounding areas of the implantation sites and liver with an average concentration of 11 ng/g, 2,1 ng/g and 1,6 ng/g respectively. The 17 ß-trenbolone residue was only detected in tissue of inner area of the implantation site at the average concentration of 8,2 ng/g. Meanwhile, none of the residues were detected in urine. Key Words: Residue, Trenbolone, Implantation